Studiendarlehen für siebenbürgische Studierende im Reformationszeitalter. Eine kaum bekannte Bistritzer Quelle aus den Jahren 1565-1626 - GÜNDISCH, Konrad G.; DINCĂ, Adinel C. (Studia Universitatis Babeș-Bolyai Historia, 2019)
The present paper deals with a very important written source regarding the history of higher education in northern Transylvania from 1565 to 1626, a register with loan contracts concerning money necessary for university education abroad. The agreements were made between the Lutheran Bistrița-Chapter, on the one side, and young men and their guarantors, on the other. Only selectively and superficially discussed by previous scholars in the 19th century, exclusively from the perspective of the development of local education in and around Bistrița, the source material bears a greater significance in terms of the efforts made by the local church and community to establish and perpetuate its own intelligentsia, regardless of the social and economic background of the gifted young men who intended to complete their education. The authors of the study address the following questions: who established the educational fund, who administered the money, who were the beneficiaries and their guarantors, and under which circumstances was money awarded. The information provided by the Bistrița-register is integrated into a larger prosopographical picture of the individuals mentioned, the majority related to the Church of the Bistrița region, and it is evaluated also from a cultural point of view, the notarial structuring of the contracts, the autograph writing and the use of the personal seals recording a highly developed literate and legal mentality with strong roots in the late medieval, pre-Reformation, tradition. The present investigation intends to contribute to a deeper understanding of the support given to students by Transylvanian communities in order to build an intellectual elite educated in Central and Western Europe. Rezumat: Împrumuturi de studiu pentru studenți transilvăneni în epoca Reformei. Un izvor bistrițean puțin cunoscut, din anii 1565-1626. Textul de față se ocupă de o sursă scrisă deosebit de importantă pentru istoria educație superioare în Transilvania de Nord în intervalul delimitat de anii 1565 și 1626, fiind vorba mai precis de un registru care reunește contracte de împrumut pentru finanțarea studiilor universitare în străinătate. Contractele erau încheiate între Biserica Luterană, Capitlul Bistrița și tineri, alături de garanții lor. Această sursă, studiată parțial și superficial în veacul al XIX-lea, discutată strict din perspectiva evoluției învățământului local bistrițean, are o semnificație mai mare referitoare la eforturile făcute de comunitate pentru a-și constitui și perpetua propria elită intelectuală, indiferent de condiția social-economică a tinerilor capabili și dornici de a-și definitiva formarea. Autorii studiului tratează următoarele probleme: cine a constituit fondul destinat educației, cine a administrat banii, cine au fost beneficiarii și garanții, în ce condiții s-au acordat împrumuturile. Informația furnizată de registrul bistrițean este integrată într-un tablou prosopografic mai amplu referitor la indivizii pomeniți, majoritatea oameni ai bisericii din regiune, și este, de asemenea, evaluată dintr-o perspectivă culturală. Concepția notarială a contractelor de împrumut, scrierea autografă și recursul la sigilii personale documentează o dezvoltată mentalitate literată și juridică, cu adânci rădăcini în tradițiile medievale, de dinainte de Reforma protestantă. Analiza de față dorește să contribuie la înțelegerea mai profundă a sprijinului acordat de către comunitățile ardelene unor studenți în vederea constituirii unei elite intelectuale educate în Europa Centrală și Occidentală. Cuvinte cheie: Transilvania, Bistrița, Biserica Luterană, universitate, credit de studiu, registru.